Workload of a new district AIDS counselling unit, April 1987 to March 1988. Issue 2 (April 1989) - Bor, R; Elford, J; Miller, R; Perry, L; Salt, H
Abstract : The Hampstead district AIDS counselling unit in London was opened in January 1987. It is staffed by a clinical psychologist, a social worker, and an administrator. From April 1987 to March 1988, 141 new patients and their relatives were referred from a range of clinical departments and 544 counselling sessions were provided. In addition, 666 staff consultations were organised to help colleagues manage some of the psychosocial problems of patients. An increase in demand during 1988-89 and a need for additional resources are anticipated. A strong case is seen for training other members of health care teams so that they may counsel patients with AIDS without referring them to the unit.